2021
DOI: 10.1177/0956462420987447
|View full text |Cite
|
Sign up to set email alerts
|

Fertility intentions of women living with HIV and their male partners during the perinatal period in rural South Africa

Abstract: Understanding the fertility intentions of people living with HIV can guide safer conception planning and prevention of mother-to-child transmission (PMTCT). Most research has addressed fertility intentions among women, rather than couples, at a single time point. This clinical trial of a PMTCT intervention in rural Mpumalanga province, South Africa, examined longitudinal fertility intentions among perinatal women living with HIV and their male partners. Study assessments and intervention and control sessions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Our results are consistent with those of other related studies conducted in Malawi, Ethiopia and South Africa that found that fertility intentions among women reduced with age. 1 , 13 , 21 , 31 Furthermore, our findings also agree with earlier studies which observed that fertility intention reduced by 12.9% among women who had 2–3 children. 31 , 42 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with those of other related studies conducted in Malawi, Ethiopia and South Africa that found that fertility intentions among women reduced with age. 1 , 13 , 21 , 31 Furthermore, our findings also agree with earlier studies which observed that fertility intention reduced by 12.9% among women who had 2–3 children. 31 , 42 …”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with those of other related studies conducted in Malawi, Ethiopia and South Africa that found that fertility intentions among women reduced with age. 1,13,21,31 Furthermore, our findings also agree with earlier studies which observed that fertility intention reduced by 12.9% among women who had 2-3 children. 31,42 Our study findings have also shown that mothers living without HIV in marital union had higher likelihood of fertility intentions compared to mothers who were never married.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The research found that females' fertility intentions was significantly lower than males' (Shreffler et al, 2016) and males preferred their child to be a girl while females preferred boy (Dhande & Shingare, 2016). The fertility intention of rural residents was significantly higher than urban residents (Mandel et al, 2021). And high-income groups tended to have more children (Shreffler et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, factors such as increased dyadic motivation have been observed to in uence the reproductive intentions of couples in early ART among HIV-positive East Africans 18 . When a partner lacks a comparable motive to one's own, this disparity may be indicative of a negative fertility goal since it generates inconsistency and does not legitimize one's choice 19 . The incongruence of the partner's reproductive motive elicits and combats unpleasant feelings through this mechanism.…”
Section: Congruence In Fertility Motivation Between Husband and Wifementioning
confidence: 99%